Causes of Landslide and its Socio-economic Effects: a study on Chattogram City and Surrounding Areas, Bangladesh - Md. Jahangir Ali (Yayasan Ilomata, 2021)
Landslide is a regular hazard in Bangladesh especially in Chattogram, the South-Eastern part of the Country. In 2007 and 2008 there happened two massive landslides in Chattogram. As a result, a huge number of people (130 and 11 respectively) died with heavy loss of properties affecting thousands of people in the region. Most of the landslides happened after torrential rain. Combined effect of rainfall and hill cutting induced slope instability adding Earthquake-triggered landslide in Chattogram. Some influential people are involved in hill cutting and developing hilly settlements in Chattogram. In some places, Government and non-Government authorities are developing settlements by razing hills there. A detailed area planning, landslide vulnerability zoning, landslide database development, geophysical analysis, and strictly implementation of Government’s existing rules are recommended to ensure avoiding further tragedy in Chattogram like 2007 and 2008.